Preoperative and intraoperative neuromonitoring and mapping techniques impact oncological and functional outcomes in supratentorial function-eloquent brain tumours: a systematic review and meta-analysisResearch in context - Asfand Baig Mirza; Amisha Vastani; Rishabh Suvarna; Sami Rashed; Aws Al-Omari; Engelbert Mthunzi; Feras Fayez; Nicala Rampersad; Josephine Jung; Alba Díaz Baamonde; José Siado Mosquera; Ali Elhag; et al. (EClinicalMedicine)
Summary: Background: Supratentorial function-eloquent brain tumour surgeries challenge the balance between maximal tumour resection and preservation of neurological function. This study aims to evaluate the efficacy of preoperative and intraoperative mapping techniques on resection outcomes and post-operative deficits. Methods: This systematic review and meta-analysis examined literature up to March 2023, sourced from PubMed, Embase, and Medline. Criteria for inclusion were studies on patients undergoing surgery for supratentorial brain tumours, comparing preoperative mapping only (POM), intraoperative neuromonitoring and mapping (IONM), and combined techniques (POM&IONM), excluding non-randomized controlled trials. Data extraction focused on rates of gross total resection (GTR) and focal neurological deficits (FNDs). The main outcomes, assessed through a random-effects model and Cochran's Q-test for subgroup analysis. The study protocol is published on PROSPERO CRD42024512306. Findings: 19 studies involving 992 patients were included. Systematic review with meta-analysis revealed a non-significantly higher average GTR rates for POM&IONM (49.13%) and POM (50.79%) compared to IONM alone (41.23%). Highest rates of GTR were achieved with tractography-guided resection in POM group (66.59% versus fMRI–20.00%, p = 0.0004), multimodal stimulation in IONM group (54.16% versus low frequency stimulation (LFS)–13.29%, p < 0.0001) and in POM&IONM group (65.88% versus LFS–37.77%, p = 0.0036). Within the same tumour histology–metastasis, high grade and low grade glioma–there are no differences in the GTR rates achieved in the different groups (p > 0.05). In language-eloquent tumours and in awake craniotomy techniques regardless of tumour functional eloquence, POM&IONM group had higher GTR when compared to IONM groups (language eloquent tumours–POM&IONM 43.31% versus IONM–15.09%, p = 0.022; awake craniotomy technique–POM&IONM–41.22% versus IONM–12.08%, p = 0.0006). Permanent FNDs were higher in the IONM group (IONM-73.0%; POM-29.6%; POM&IONM-33.7% of immediate postoperative deficits, p = 0.0010). Interpretation: A combined POM&IONM approach is responsible for higher rates of GTR in patients with language eloquent tumours and in both awake and asleep craniotomy techniques regardless of the tumour functional eloquence. The tumour histology is not relevant for differences in GTR rates among different mapping and monitoring strategies. Permanent postoperative FNDs are more likely with standalone utilization of IONM. Funding: Not applicable.